2009
DOI: 10.1249/mss.0b013e3181a48ee6
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Patterns Measured by Accelerometry in 6- to 10-yr-Old Children

Abstract: The decline in PA in children may start already at the age of 6 yr. The school setting may be an important arena for targeting activity levels in girls because the difference in PA levels between girls and boys is most pronounced during school time. In both girls and boys, PA levels are disproportionally low during weekends and might be important targets for interventions aimed to increase PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 40 publications
10
74
0
6
Order By: Relevance
“…Several studies have noted the importance of the school day for PA accumulation among elementary-aged children, with students accumulating significantly greater MVPA during the school day compared with time spent at home and children participating in significantly greater sedentary time at home compared with time spent in school. [32][33][34] In addition, children encouraged to be physically active in school have been shown to be more active outside of school compared with children whose school-day PA was restricted, and other studies have shown children to be more active during the school week compared with weekend days. [35][36][37] These findings, in concert with the weak correlation between parent-child PA levels, corroborate the importance of school-day PA.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have noted the importance of the school day for PA accumulation among elementary-aged children, with students accumulating significantly greater MVPA during the school day compared with time spent at home and children participating in significantly greater sedentary time at home compared with time spent in school. [32][33][34] In addition, children encouraged to be physically active in school have been shown to be more active outside of school compared with children whose school-day PA was restricted, and other studies have shown children to be more active during the school week compared with weekend days. [35][36][37] These findings, in concert with the weak correlation between parent-child PA levels, corroborate the importance of school-day PA.…”
Section: Discussionmentioning
confidence: 99%
“…This is more obvious when the comparison is conducted among boys of 6 years of age; at that age, the prevalence of obesity is 18.8% and 22.7% (p = .002) among the most and least vulnerable children respectively. Obesity prevalence in Chilean preschool children increases with age (Kain et al 2009), probably due to a greater intake of less healthy, processed foods and a decline in physical activity which has been shown to begin already at 6 years of age (Nyberg et al 2009). In addition it has been demonstrated that there is a reduction in vigorous physical activity as children grow older, aspect shown to be more associated with adiposity than sedentarism (Steele et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, el estudio encontró que a mayor edad disminuye la intensidad de AF, este hallazgo refrenda lo encontrado en el estudio IDEFICS (23) en niños europeos que muestra una disminución de la actividad física a medida que avanza la edad, a partir de los 4 años. Al igual que un estudio sueco (27) , que indica que la AF declina entre los 5 y 10 años.…”
Section: Discussionunclassified